2008
DOI: 10.1016/j.nbd.2008.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation and catabolism of disease-associated intra-Aβ mutations: reduced proteolysis of AβA21G by neprilysin

Abstract: Five point mutations within the amyloid β-protein (Aβ) sequence of the APP gene are associated with hereditary diseases which are similar or identical to Alzheimer's disease and encode: the A21G (Flemish), E22G (Arctic), E22K (Italian), E22Q (Dutch) and the D23N (Iowa) amino acid substitutions. Although a substantial body of data exists on the effects of these mutations on Aβ production, whether or not intra-Aβ mutations alter degradation and how this relates to their aggregation state remain unclear. Here we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
90
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(99 citation statements)
references
References 51 publications
(61 reference statements)
9
90
0
Order By: Relevance
“…2j and 4d). These observations are in accordance with previously published reports showing that Arctic (E22G) and Dutch (E22Q) mutations in Aβ significantly increase fibril nucleation and growth, whereas the Flemish (A21G) mutation decreases fibril growth 85 .…”
Section: Preparation and Characterization Of A40 Protofibrilssupporting
confidence: 93%
See 1 more Smart Citation
“…2j and 4d). These observations are in accordance with previously published reports showing that Arctic (E22G) and Dutch (E22Q) mutations in Aβ significantly increase fibril nucleation and growth, whereas the Flemish (A21G) mutation decreases fibril growth 85 .…”
Section: Preparation and Characterization Of A40 Protofibrilssupporting
confidence: 93%
“…Figure 4 summarizes the results of these studies. Aβ40-Arctic (E22G) exhibits faster aggregation kinetics than does wt Aβ40 and has a higher tendency to form and accumulate protofibrils 18,36,85 . Accordingly, we found that dissolving synthetic Aβ40-Arctic in DMSO (Step 1B) resulted in a solution that is highly enriched with protofibrils and monomeric Aβ.…”
Section: Preparation and Characterization Of A40 Protofibrilsmentioning
confidence: 99%
“…Thioflavin T Binding Assay-Aggregation of Bri and ABri was monitored using a continuous thioflavin T (ThT) binding assay (21). Peptides were diluted to the desired concentration with the appropriate SEC elution buffer and ThT was added from a ϫ100 stock solution to a final concentration of 20 M. Aliquots (120 l) of the peptide solutions were then dispensed into the wells of an ice-cold 96-well black microtiter plate (Nunc, Roskilde, Denmark) and read immediately.…”
Section: Methodsmentioning
confidence: 99%
“…Electron Microscopy-Peptide samples were prepared as for the ThT binding assay, but in the absence of ThT, and analyzed by negative contrast microscopy as previously described (21 Circular Dichroism (CD) Spectroscopy-Peptide solutions in 20 mM NaP, pH 8.0, were analyzed at 22°C in a 1-mm quartz cuvette (Starna Scientific, Hainault, UK) using a J-810 JASCO spectropolarimeter (JASCO Corp., Tokyo, Japan). Spectra were collected from three data accumulations between 190 and 260 nm with 10 nm/min continuous scanning and 1 nm bandwidth.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, NEP, ACE, and plasmin are considered to be physiologically and pathologically relevant in sporadic AD. NEP is a membrane-bound zinc metallopeptidase localized at the cell surface and in cytoplasmic vesicles preferentially hydrolyzing extracellular oligopeptides on the amino side of hydrophobic residues (53) and has been shown to be capable of degrading A␤ both in vivo (54,55) and in vitro (55)(56)(57). NEP is also reported to be expressed on neuronal pre-and postsynaptic membranes (52).…”
Section: Maldi-tof-ms Analysis Of Cleavage Products Of Npa␤ and Pa␤mentioning
confidence: 99%